The Creation of Muhajirat in America: Social Media as a Platform for Crafting Gender-Specific Interventions for the Domestic Radicalization of Women, 5 countries, 1970-2018 - Warren, Janet I. ([Verlag nicht ermittelbar], 2021)
This study examines the radicalization of Western women to extremist violence, both through the creation of a moral-situational-action risk model and the examination of their responses to various types of online propaganda. The Moral-Situational-Action Risk Model for Extremist Violence (MSA-RMEV) was developed using situational action theory from criminology and violence risk practice literature. The MSA-RMEV revolves around three domains reflective of propensity, mobilization, and capacity building, geared towards providing a violence risk assessment that can assist the intelligence community in preventing future acts of violence. A sample of women who self-identified as conservative, liberal, and Muslim were exposed to jihadist, alt-right, and alt-left online propaganda. Physiological responses and self-report assessments were recorded. Eye-gaze, pupil dilation, galvanic skin response, heart rate, and facial emotions were documented, along with women's judgment of their emotional, cognitive, and arousal states, while viewing propaganda. Based on their results, women were categorized as high-risk, medium-risk, or low-risk for violence. Additionally, numerous variables were created to identify participant's beliefs and behavior related to radicalization. Beliefs included religiosity, political affiliation, the presence of moral emotions, sacred values, developmental maturity, and militant thinking. Behaviors included group affiliations, extent of involvement in extremist activities, and presence on social media platforms such as Facebook, Reddit, and Twitter. Demographic variables such as age, marital status, number of children, race, ethnicity, country of origin, and educational status were included.